Representation of Women's Image in Iranian Contemporary Painting (A Study Based on Michel Foucault's Concept of Power) - Mohajeri, Mahdis; Fahimifar, Asghar (Advances in Social Sciences Research Journal, 2018)
By examining the representation of women in Iranian painting, it is presumable that through Iranian painting history the perspective toward role of women was often passive. This representation is somehow symbolic and idealistic defining stereotypes attributed to women. What is notable is permanency of the idealist and symbolic attitude toward women, while these roles are sometimes far from the personal experiences of women. One major constitution which can form and classify people is community. The society’s Dominant cultures impact on the way identities of individuals reveal in a society. Since the art is intertwined with a society created in, it can be stated that the rise of dominant paradigms on women social and cultural conditions can be reviewed in art and specifically in this study in contemporary art. Therefore, it could claim that governor social power has an effective role for shaping identities in a community. Many theorists presented their insights about power and argued about different shapes and organs of power. Michel Foucault was equally a philosopher a psychologist and a historian. The power concept is central to his thinking regarding the relations between society, individuals, groups and institutions. Foucault had an aim to examine how power operates in daily interactions between people and institutions. This research tries to answer the question that how power relations define woman as human being subjects in Iranian contemporary painting, and what's more, how women resist power applying to their lives, besides how they develop their strategy in their painting? The results of this research which are gained by analytical- descriptive method indicates that female painters unlike male artists, when depicting a woman, do not consider well-known features beauties of a woman, showing their body, hair and lips etc. They avoid pointing out formal feminine features. Instead they focus on inner configuration.